Workplace mindfulness: fundamental issues for research and practice. (3rd April 2021) - Shahbaz, Wahab; Parker, Jane
ABSTRACT: In organisational scholarship, there is a general understanding that mindfulness training programs (MTP) can guide employees' cognitive and psychological processes and influence their decisions and actions in everyday life. Many organisations who care for the wellbeing and development of employees are adopting MTP as a tool to improve employees' functions such as their health and performance. In this research note, some of the key issues concerning mindfulness theory and practice are highlighted. First, multiple perspectives on mindfulness exist in the literature and also the boundaries between secular and non-secular practices of mindfulness are unclear. To extend the theory and practice of mindfulness, it is important to comprehend the concept of mindfulness. Second, MTP can be costly rather than beneficial in some working conditions. The managers might need to understand the risk related to the negative consequences of MTP. Third, sustainability of mindfulness practices for employees in a post-training context might be challenging. Managers might need to develop and maintain a conducive post-training work environment that encourages the employees' mindfulness practices at work. Overall, this research note suggests research directions for management scholars and informs the organisational leaders' and managers' decisions concerning the incorporation of MTP in organisations for employees' wellbeing and development.